O‗qituvchilarni tarixiy materiallar vositasida vatanparvarlik ruhida tarbiyalashning pedagogik imkoniyatlari - Kosbergenov, R.M (SCIENCE and SOCIETY, 2024)
The article talks about improving the process of educating young people and future teachers in the spirit of patriotism
Keywords: patriotism; history; pedagogy; education; personality; nationality; spirituality; culture